2005
DOI: 10.5794/jjoms.51.614
|View full text |Cite
|
Sign up to set email alerts
|

A case of basaloid squamous cell carcinoma of the floor of the mouth-Estimation of proliferative activity by Ki-67 immunohistochemical staining-

Abstract: Basaloid squamous cell carcinoma was first reported by Wain et al. in 1986 and has recently been designated a variant of squamous cell carcinoma because of its high potential for distant metastasis. We report a case of basaloid squamous cell carcinoma arising in the floor of the mouth in a 74-year-old man. The proliferative activities of this case and another case previously reported by our department were compared with those of 21 cases of poorly differentiated squamous cell carcinoma. The cases of basaloid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The frequency of occurrence is as low as 2%‐5% of all head and neck cancers 6,9 . In this study, we reviewed 27 cases of OBSCC reported in Japan between January 2001 and January 2020 10‐34 (Table 1). According to the present study, the incidence was the highest in those in their 60s, with men accounting for most patients.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of occurrence is as low as 2%‐5% of all head and neck cancers 6,9 . In this study, we reviewed 27 cases of OBSCC reported in Japan between January 2001 and January 2020 10‐34 (Table 1). According to the present study, the incidence was the highest in those in their 60s, with men accounting for most patients.…”
Section: Discussionmentioning
confidence: 99%